Immunotherapeutic treatment of inflammation in mice exposed to methamphetamine - Loftis, Jennifer M.; Ramani, Sankrith; Firsick, Evan J.; Hudson, Rebekah; Le-Cook, Anh; Murnane, Kevin S.; Vandenbark, Arthur; Shirley, Renee L. (Frontiers in Psychiatry, 2023)
Introduction Currently, there are no FDA-approved medications to treat methamphetamine addiction, including the inflammatory, neurotoxic, and adverse neuropsychiatric effects. We have shown that partial (p)MHC class II constructs (i.e., Recombinant T-cell receptor Ligand – RTL1000), comprised of the extracellular α1 and β1 domains of MHC class II molecules linked covalently to myelin oligodendrocyte glycoprotein (MOG)-35-55 peptide, can address the neuroimmune effects of methamphetamine addiction through its ability to bind to and down-regulate CD74 expression, block macrophage migration inhibitory factor (MIF) signaling, and reduce levels of pro-inflammatory chemokine ligand 2 (CCL2). The present study evaluated the effects of our third-generation pMHC II construct, DRmQ, on cognitive function and concentration of inflammatory cytokines in the frontal cortex, a region critical for cognitive functions such as memory, impulse control, and problem solving. Methods Female and male C57BL/6J mice were exposed to methamphetamine (or saline) via subcutaneous (s.c.) injections administered four times per day every other day for 14 days. Following methamphetamine exposure, mice received immunotherapy (DRmQ or ibudilast) or vehicle s.c. injections daily for five days. Cognitive function was assessed using the novel object recognition test (NORT). To evaluate the effects of immunotherapy on inflammation in the frontal cortex, multiplex immunoassays were conducted. ANOVA was used to compare exploration times on the NORT and immune factor concentrations. Results Post hoc analysis revealed increased novel object exploration time in MA-DRmQ treated mice, as compared to MA-VEH treated mice (non-significant trend). One-way ANOVA detected a significant difference across the groups in the concentration of macrophage inflammatory protein-2 (MIP-2) (p = 0.03). Post hoc tests indicated that mice treated with methamphetamine and DRmQ or ibudilast had significantly lower levels of MIP-2 in frontal cortex, as compared to mice treated with methamphetamine and vehicle (p > 0.05). Discussion By specifically targeting CD74, our DRQ constructs can block the signaling of MIF, inhibiting the downstream signaling and pro-inflammatory effects that contribute to and perpetuate methamphetamine addiction.